EFEK PEMBERIAN BLANKET WARMER TERHADAP THERMOREGULASI PASIEN PERIOPERATIF TRANSURETHRAL RESECTION OF THE PROSTATE (TURP) - Firmansyah, Doddy; Nursanti, Irna; Irawati, Diana; Jumaiayah, Wati (Jurnal Perawat Indonesia, 2022)
Perioperatively in BPH patients who underwent TURP action caused thermoregulation disturbances which resulted in a decrease in temperature (hypothermia). This can occur due to exposure to environmental temperatures that are too extreme and the effects of anesthetic drugs during intraoperatively which can cause vasodilation of blood vessels and blocked sympathetic nerves so that they dominate the performance of the parasympathetic nerves. The purpose of the study was to determine the effectiveness of the Blanket Warmer in perioperative TURP patients at the Central Surgical Installation of Tarakan Hospital, Jakarta. The design of this study used a quasi-experimental pretest-posttest with control group design. The research sample was 48 respondents of TURP perioperative patients. The sampling technique was accidental sampling, the statistical test used was Paired t test. The results of the univariate analysis showed that the highest age was 50 years, about 89%, a history of drug consumption 54.2%, and a history of alcohol consumption as much as 29.2%. Bivariate test analysis between the intervention group and the control group obtained a p value of 0.001 <0.05, which means that there is a significant difference in the two groups. The multivariate test obtained p value > 0.05, meaning that the variables of age, history of drug consumption and history of alcohol consumption did not have a significant effect on thermoregulation stability. That there is an effect of giving a Blanket Warmer on the stability of thermoregulation in perioperative TURP patients. Suggestions for further research that a blanet warmer can stabilize thermoregulation in perioperative TURP patients at the Central Surgical Installation of Tarakan Hospital Jakarta. Keywords: TURP, Blanket Warmer, Thermoregulation Stability